USP7 Promotes deubiquitination and stabilization of MyD88 to enhance immune responses - Zhang, Na; Wang, Fei; Zhang, Gaomeng; Zhang, Qi; Liu, Yuhong; Wang, Qiao; Elsharkawy, Mohamed Shafey; Zheng, Maiqing; Wen, Jie; Zhao, Guiping; Li, Qinghe (Frontiers in Immunology, 2022)
Toll-like receptors (TLRs) are involved in the sensing of pathogen-associated molecular patterns (PAMPs) such as lipopolysaccharide (LPS), flagellin, unmethylated double-stranded DNA (CpG), single-stranded RNA (ssRNA) and lipoproteins. Myeloid differentiation primary response protein 88 (MyD88) is a canonical adaptor for the Toll-like receptor family which has crucial roles in host defense against infection by microbial pathogens. The dysregulation of MyD88 may also induce autoimmune diseases. Here, we demonstrate that the deubiquitinase USP7 interacts with MyD88 in chicken, with knockdown or overexpression of USP7 leading to the regulation of MyD88 protein in a positive manner. Consequently, USP7 positively regulates the expression of proinflammatory factors upon LPS challenge. Furthermore, we observed USP7-deficient mice to be more susceptible to infection by Salmonella typhimurium. Collectively, our findings demonstrate MyD88 as a bona fide substrate of USP7 and uncover a mechanism by which USP7 regulates innate immune signaling.